ARAP GRAMERİNDE TE'KİD - SEZER, MEHMET ALİ (Fırat Üniveristesi, 2003)
Yüksek Lisans Tezi ARAP GRAMERİNDE TE'KİD Mehmet Ali SEZER Sosyal Bilimler Enstitüsü Temel İslam Bilimleri Ana Bilim Dalı Arap Dili ve Belagatı Bilim Dalı 2003; Sayfa:90 Te'kid, Arapça cümle yapısında yardımcı öğeler olan tevabi 'dendir. Cümlenin anlamını pekiştiren te'kid tekrarlarla yapılır. Bu da iki şekilde olur: Birincisi lafzın tekrarıyla yapılır ki buna lafzi te'kid denir. İkincisi ise mananın tekranyla yapılır ki buna da manevi te'kid denir. Ancak her tekrar te'kid değildir. Çünkü te'kid tekrarın bir kısmını oluşturur. Te'kidin amacı söylenen sözün tam an lası İm ası dır. Verilmek istenen mesaj tam anlaşılmadığı zaman te'kid yapılır. Te'kid yapılırken muhatabın durumu dikkate alınır. Bunun için te'kidin derecesi muhatabın tavrına göre değişir. Te'kidde tabii'yet esas alınmış, tabi olan ve olmayan şeklinde ikiye ayrılmıştır. Anahtar Kelimeler: Te'kid, tekrar, lafzi, manevi, kelime ve tabii'yet

SUMMARY Masters Thesis TE'KİD IN THE ARABIC GRAMMER Mehmet Ali SEZER Fırat University The Institute of Social Science The Department of Basic islamic Science The Arabic Language And Its Rehetoric 2003; 90 Page Te'kid is from repetition which contributes the sentences structure in Arabic. Te'kid that strengthens the meaning of sentence is done by repetitions. The one that is done by statement is called the statement te'kid, an the one which is done by help of the repetition of the meaning is called spiritual te'kid. Every repetition is not the tekid, because te'kid consistes only some of the repetation. The aim of the te'kid is to understand the whole menaing of the sentence. When the message is not understood well the te'kid is done. When the te'kid is done the situation of the collocutor is regarded.. That is why the degree of the te'kid changes according to the situation of the colloctur. The followness is essential in the te'kid and the subject the te'kid dealt has been sorted out in to groups. The following one an the non-following one. Key words: Te'kid, repetation, statement, spiritual, word, followness.
Te`kid the Arabic gramer
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Doğu Dilleri ve Edebiyatı; Eastern Linguistics and Literature